2008
DOI: 10.1177/102425890801400308
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the European Works Council deficit in German multinationals

Abstract: This article examines the problem of setting up European Works Councils in German multinationals. Based on the findings of a Hans-Böckler-Stiftung funded project, the article argues that a key problem is the legal status of many German companies covered by the European Works Councils Directive: specifically, that companies in private hands are not legally required to reveal the number of their employees and their company structure. This lack of transparency makes it very difficult for employee representatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
0
9
0
2
Order By: Relevance
“…Our research is inspired by earlier findings for German MNCs (Whittall et al, 2008). It has been assumed that a company's information disclosure policy, especially on staff numbers in different countries, is a crucial factor influencing the establishment of an EWC: for many smaller MNCs, it is not clear whether they meet the thresholds of the directive.…”
Section: Swiss Companies With An Ewcmentioning
confidence: 99%
“…Our research is inspired by earlier findings for German MNCs (Whittall et al, 2008). It has been assumed that a company's information disclosure policy, especially on staff numbers in different countries, is a crucial factor influencing the establishment of an EWC: for many smaller MNCs, it is not clear whether they meet the thresholds of the directive.…”
Section: Swiss Companies With An Ewcmentioning
confidence: 99%
“…In previous work we have suggested that the reason for actors' knowledge of the Directive's applicability relates to the question of a lack of transparency within privately owned enterprises (Lücking et al ., 2008; Whittall et al ., 2008). With the number of privately owned German companies covered but not possessing an EWC standing at around 80 per cent, one explanation we chose concerns the fact that non‐shareholder companies are not required to make information on management structures and revenue flows public.…”
Section: Knowledge Deficitmentioning
confidence: 99%
“…The characteristics of MNCs with no EWC are becoming clearer: they tend to be smaller and with operations in private sector services (De Spiegelaere and Jagodzinski, 2015). Employee representatives based in the home country of some MNCs have rejected requests from their counterparts in foreign subsidiaries to establish an EWC, on the grounds that it would dilute existing relationships with central management (Whittall et al, 2008(Whittall et al, , 2015. A further task for research is thus be to examine if or how union organizations have responded to such situations.…”
Section: Actorsmentioning
confidence: 99%